Sliding Mode Control Design for Magnetic Levitation System - Ma'arif, Alfian; Vera, Marco Antonio Marquez; Mahmoud, Magdi Sadek; Umoh, Edwin; Abougarair, Ahmed Jaber; Rahmadhia, Safinta Nurindra (Journal of Robotics and Control (JRC), 2022)
This paper presents a control system design for a magnetic levitation system (Maglev) or MLS using sliding mode control (SMC). The MLS problem of levitating the object in the air will be solved using the controller. Inductors used in MLS make the system have nonlinear characteristics. Thus, a nonlinear controller is the most suitable control design for MLS. SMC is one of the nonlinear controllers with good robustness and can handle any model mismatch. Based on simulation results with a step as input reference, MLS provided good system performances: 0.0991s rise time, 0.1712s settling time, and 0.0159 overshoot. Moreover, a prominent tracking control for sine wave reference was also shown. Although the augmented system had a chattering effect on the control signal, the chattering control signal did not affect MLS performances.